Remifentanil attenuates endoplasmic reticulum stress and inflammatory injury in LPS-induced damage in HK-2 cells. Issue 1 (31st December 2022) - Yan, Yixiu; Zhu, Na; Jin, Dan; Lin, Feihong; Lv, Ya
Abstract: Renal injury is a fatal complication in critically ill patients with sepsis. As an ultrashort-acting synthetic opioid derivative, remifentanil has been reported to mitigate renal injury and sepsis. Nevertheless, whether remifentanil also suppresses sepsis-triggered renal injury is uncertain. The aim of this study was to investigate the effect of remifentanil on endoplasmic reticulum stress (ERS) and inflammatory response in an in vitro lipopolysaccharide (LPS)-stimulated renal tubular epithelial cell (HK-2) model and its mechanism. The viability of HK-2 cells with the absence or presence of LPS treatment was surveyed by cell counting kit-8 assay. Under the condition of LPS treatment, apoptosis was appraised by TUNEL assay and western blot. Levels of inflammatory factors were estimated though corresponding kits. Western blot tested the expression of toll-like receptor 4 (TLR4)/nuclear factor-kappaB (NF-κB) signaling-associated proteins. Also, the expression of ERS-related proteins was detected by western blot. Further, ERS inducer tunicamycin (TM) was added and the aforementioned experiments were conducted again. The results underlined the protective effects of remifentanil on LPS-evoked viability injury, inflammation, activation of TLR4/NF-κB signaling and ERS in HK-2 cells. Moreover, the impacts of remifentanil on the biological events of LPS-insulted HK-2 cells were all reversed by TM administration. To conclude, remifentanil might have a remarkable ameliorative effect on sepsis-induced renal injury, which implied the potential of remifentanil-based drug therapy in sepsis-induced renal injury.